Hard template synthesis of metal nanowires - Kawamura, Go; Muto, Hiroyuki; Matsuda, Atsunori (Frontiers in Chemistry, 2014)
Metal nanowires (NWs) have attracted much attention because of their high electron conductivity, optical transmittance and tunable magnetic properties. Metal NWs have been synthesized using soft templates such as surface stabilizing molecules and polymers, and hard templates such as anodic aluminum oxide, mesoporous oxide, carbon nanotubes. NWs prepared from hard templates are composites of metals and the oxide/carbon matrix. Thus, selecting appropriate elements can simplify the production of composite devices. The resulting NWs are immobilized and spatially arranged, as dictated by the ordered porous structure of the template. This avoids the NWs from aggregating, which is common for NWs prepared with soft templates in solution. Herein, the hard template synthesis of metal NWs is reviewed, and the resulting structures, properties and potential applications are discussed.